Alpha Brain Wave Activity during Listening of Surah Al-Insyiqaq using Electroencephalography (EEG) - Ahmad Azwar Habibi; Ully Husna; Khusnul Khatima; Annisah Nur Rahmah; Aditya Rizqi Darmawan (The Avicenna Medical Journal, 2020)
Background: More than 30 times earthquake occurred in Indonesia in the periode 2016-2017 and 23 times occurred in 2018. It made people more anxious. This is also a warning of the coming of the doom which is explained in several verses of the Qur'an. One of them is surah al-Insyiqaq. Understanding the meaning of this surah is expected to increase anxiety or feelings of surrender. These emotions can affect brain activity and can be recorded withElectroencephalography (EEG). To date, there has been no specific study of alpha wave activity when surah al-Insyiqaq is played between groups who understand the meaning of the surah and those who do not understand.Objective: Comparing the alpha brain wave activity during listening surah al-Insyiqaq in the control group and the treatment group.Method: This research is a study using experimental methods conducted on 20 subjects using simple random sampling. Subject were divided into two groups, the control group, and the treatment group. The treatment group was given a booklet, video and lecture about the contents of the surah. Brain wave activity was measured before and after the intervention using EEG during the subject listens to murottal of the surah.Results: There is a significant difference in understanding the meaning of Surat al-Insyiqaq between the results of the post test control group and the treatment group that was previously given the intervention (p=0,041). The significance value of the difference in alpha wave activity in the two groups was performed using the Independent t test and obtained p = 0.033.Conclusion: Understanding surah al-Insyiqaq creates a feeling of calm and surrender to God. This can lead to greater alpha brain wave activity when listening to surah al-Insyiqaq than those who are not given an understanding of the meaning of surah al-Insyiqaq.